TO INVESTIGATE THE TREND AND EXPANSION OF PRIVATE EQUITY INVESTMENT IN INDIA - Lakhotia, Rithvik (Indian Journal of Finance and Banking, 2023)
This paper delves into India’s burgeoning realm of private equity investment, examining its growth trends, sectoral preferences, and risk profile. Utilizing log-lin regression analysis of detailed data from 2012 to 2022, we unveil insights into deal value and volume for investments and exits. Our findings paint a nuanced picture. While India presents compelling opportunities, it also harbours inherent risks for private equity players. Notably, 2020 witnessed the highest influx and divestment of capital, highlighting the dynamic nature of the market. Construction, information technology, and real estate are the hottest sectors, attracting significant investor attention. The quantitative analysis reveals a steady annual growth of 5.4% in private equity investment value, further bolstered by a notable 3.4% weekly increase. These robust figures solidify India’s position as a burgeoning private equity hub. Furthermore, we venture beyond historical patterns, offering valuable predictions for the next ten years. This vital forecast equips investors and stakeholders with critical insights to navigate the evolving landscape of Indian private equity. In conclusion, this study comprehensively analyses private equity’s rise and inherent risks within the Indian context. Through data-driven insights and future projections, it empowers informed decision-making and strategic planning for navigating the promising yet dynamic realm of private equity in India. JEL Classification Codes: E22, L16.